Multidimensional Approach Assessing the Role of Interleukin 1 Beta in Mesial Temporal Lobe Epilepsy - Santos, Renato O.; Secolin, Rodrigo; Barbalho, Patrícia G.; Silva-Alves, Mariana S.; Alvim, Marina K. M.; Yasuda, Clarissa L.; Rogerio, Fábio; Velasco, Tonicarlo R.; Sakamoto, Americo C.; Teixeira, Antonio L.; Cendes, Fernando; Maurer-Morelli, Claudia V.; et al. (Frontiers in Neurology, 2021)
We aimed to investigate the role of interleukin-1 beta (IL-1β) in the mechanisms underlying mesial temporal lobe epilepsy with hippocampal sclerosis (MTLE+HS). We assessed a cohort of 194 patients with MTLE+HS and 199 healthy controls. Patients were divided into those with positive and negative antecedent febrile seizures (FS). We used a multidimensional approach, including (i) genetic association with single nucleotide polymorphisms (SNPs) in the IL1B gene; (ii) quantification of the IL1B transcript in hippocampal tissue of patients with refractory seizures; and (iii) quantification of the IL-1β protein in the plasma. We found a genetic association signal for rs3730364*C SNP allele in the IL1B gene, regardless of the presence of FS (odds ratio for MTLE+HS with FS = 2.66, 95% confidence interval [CI] = 1.86–3.79, p = 5.14e-10; odds ratio for MTLE+HS without FS = 2.51, 95% CI = 1.72–3.66, p = 1.34e-08). We found no difference between IL1B transcript levels when comparing sclerotic hippocampal tissue from patients with MTLE+HS, without FS, and hippocampi from autopsy controls (p > 0.05). Nevertheless, we found increased IL-1β in the plasma of patients with MTLE+HS with FS compared with controls (p = 0.0195). Our results support the hypothesis of a genetic predisposition to MTLE+HS associated with the IL1B gene.